Association of aerobic capacity and muscular strength with health-related quality of life in adolescents: A school-based cross-sectional study - Bianca Lins dos Santos; João Paulo Rodrigues dos Santos; José Damião Saraiva Gomes-Júnior; Eriston de Souza Bezerra; Samuel Lira da Silva Barbosa; Bárbara Gicélia da Silva Araújo; Fabio Thiago Maciel da Silva; João Pedro Magalhães; Vera Lúcia Zymbal; Eduardo Caldas Costa; Rodrigo Alberto Vieira Browne (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background: The independent associations of aerobic capacity and muscular strength on health-related quality of life (HRQoL), when mutually adjusted, remain understudied, particularly in adolescents. Aim: To examine the association between aerobic capacity, muscle strength, and HRQoL in adolescents. Methods: A cross-sectional design was employed, including 202 Brazilian adolescents. Aerobic capacity was assessed using the PACER test and categorized into “healthy zone”, “needs improvement”, and “at risk”. Muscle strength was evaluated through field tests, including the 90º push-up, and categorized as “healthy zone” or “needs improvement”. HRQoL was measured using the validated KIDSCREEN-27 questionnaire. A generalized gamma regression model was used to estimate coefficients (β) and 95% confidence intervals for HRQoL domains, adjusting mutually for aerobic capacity and muscle strength as predictors. Results: In the physical domain, adolescents with aerobic capacity in the healthy zone (β=11.2; p<0.001) and needs improvement category (β=8.8; p=0.007) scored higher than those in the at-risk zone. Similarly, those with muscle strength in the healthy zone scored higher than in the needs improvement category (β=6.6; p=0.012). In the psychological domain, adolescents with aerobic capacity in the healthy zone (β=8.1; p=0.002) and needs improvement (β=5.9; p=0.027) also had higher scores than those at risk, as did those with healthy muscle strength compared to needs improvement (β=4.5; p=0.043). No significant associations were found in other domains (p>0.05). Conclusion: Adequate levels of aerobic capacity and muscle strength are positively associated with HRQoL, particularly in the physical and psychological well-being domains among adolescents.